Global perspectives on the impact of mass media on electoral processes - Aririguzoh, Stella Amara, 1964- (Hershey, Information Science Reference, 2021)
"This book provides relevant theoretical frameworks and research findings from different scholars evidencing the impact of the media in specific elections in different countries of the globe"--
Includes bibliographical references and index.
Keywords: Elections -- Cross-cultural studies; Internet in political campaigns -- Cross-cultural studies; Political campaigns -- Cross-cultural studies; Social media -- Political aspects -- Cross-cultural studies; Mass media -- Political aspects -- Cross-cultural studies